Forensic Art Essentials : a Manual for Law Enforcement Artists. - Gibson, Lois (Elsevier, 2007)
The demand for forensic art usage in investigations is rapidly expanding due to media attention. Despite this fact, to date no book thoroughly explains how to sketch a suspect's face from a witness? memory. Forensic Art Essentials teaches artists to extract information from a witness or victim about a face they have seen, and produce an image good enough to lead detectives to the criminal being described. After reading this book, anyone with adequate drawing skills will be able to learn the tools necessary to develop his or her skills as a forensic artist. Instruction focuses on an explanation.